The Next Step to Further Decrease Veterinary Antibiotic Applications: Phytogenic Alternatives and Effective Monitoring; the Dutch Approach - Groot, Maria J.; Berendsen, Bjorn J. A.; Cleton, Natalie B. (Frontiers in Veterinary Science, 2021)
Antibiotics are used to control infectious diseases in both animals and humans. They can be life-saving compounds but excessive use in animal husbandry leads to the development of antibiotic resistance which can impact the public health. Since similar antibiotics are used in both animal and human healthcare, it is important to reduce the use of antibiotics in production animals. In the Netherlands policies have been developed aiming for a decrease of antibiotic usage in animals, and alternatives to antibiotics are investigated. Currently, a one-on-one relationship between farmer and veterinarian is successfully implemented and (national) registration of antibiotic usage is mandatory. Unfortunately, after a 70% decrease in antibiotic usage since 2009, this decrease is now stagnating in most sectors. Innovative strategies are required to facilitate a further reduction. One promising option is a focus on farm management and natural alternatives to antibiotics. The Dutch government has invested in the spread of knowledge of natural remedies and good animal management to support animal health via so called Barnbooks for farmers and veterinarians. Another option is the analysis of on-farm antibiotic use to prevent unregistered applications. New (bio)analytical strategies to monitor the correct and complete registration of antibiotic usage have been developed and trial-tested in the Netherlands. Such strategies support a risk-based monitoring and allow effective selection of high-risk (high antibiotic use or illegal antibiotic) users. Both effective monitoring and the availability and knowledge of alternatives is a prerequisite to achieve a further significant decrease in antibiotic veterinary usage.